HISTORY OF ISLAMIC CIVILIZATION IN INDONESIA IN THE ERA OLD ORDER PERIOD (1945-1966) - BAIQ WAHYU DINIYATI HIDAYATILLAH; ZULFI MUBARAQ (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
The history of Islamic civilization in Indonesia during the Old Order period (1945-1966) is very important to study, because at that time Indonesian figures began to try to improve the form of national and state order, especially in education. This paper aims to understand three things, firstly the conception of the ideological form of Islamic religious education. Second, the form factor of the ideology of Islamic religious education. Third, the implication of the form of ideology of Islamic religious education. This type of research is library research using primary and secondary data sources from journals that have been selected and are relevant to the title. The most important findings in research on the history of Islamic civilization during the Old Order era include three things. First, the development of the ideology of Islamic education has experienced ups and downs in the educational process. Second, Islamic education policies in Islamic boarding schools, madrasas or other institutions provide a forum for the community to carry out education without discriminatory policy behavior. Third, religious teaching materials in practice have not been fully implemented, on the grounds that Indonesia is not an Islamic country and the political instability of the conflict between nationalists and Islamists has a direct impact on the journey of education; As a result, the implementation of religious education is underestimated by the government. So that pesantren and madrasa could not become national education at that time. The contribution of this research can provide new insights about flexibility and progressiveness for the development of Islamic education.